A Living Quran Exploration of Tawassul Practices in Palu City: A Shortcut or a winding road to God's Grace? - Yamani, Gasim; Nurdin, Nurdin (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Tawassul has been practiced widely by Muslim societies. However, among Muslim community itself, the practice of tawassul has been a contraversy among who practice it and among who reject to do so. Previous studies mostly discussed the tawassul contraversy from scholars perspective, while studies on the contraversy of tawassul from Muslim society persepective is scarse. This study therefore, discusses the practice of tawassul in Palu city, Central Sulawesi from Muslim communities persepective who practice tawassul and who reject it. The aim of this study is to provide insight for academia and practitioners regerding the differences and reasons underlying the contraversy of tawassul among Muslim communities. This study was conducted using a qualitative approach and the data was gathered through direct observation and in-idepth interviews with keys Muslim figures who accept and reject tawassul. The results show that Muslim communities who accept and reject tawassul have similar argument taken from Al-Quran and hadis, but they have different interpretation on the sources. The different perception of tawassul does not caause conflict among Muslim societies in Palu. However, we also found that most of Muslim communities who reject tawassul come from academia who rely on rationality in interpreting the legality source of tawassul. Meanwhile, Muslim communities who practice tawassul come from ulama or Islamic scholar who are mostly Arabic or Middle eastern descent. In conslusion, we argue that there is no violation of the provisions of aqidah and shari'ah, as well as not sinful, both for groups that allow tawassul and those that do not practice tawassul. The essential problem lies in the different perspectives and understandings of the two groups towards the existing texts of the Qur'an and Hadith. Our study contributes to the body of knowledge within the area of quranic studies and to the Muslim communities who practice or reject tawassul.